Analisis Optimalisasi Penyusunan Laporan Kinerja Melalui Standar Pelayanan Publik (Lingkup Pemerintahan) Di Sekretariat Daerah Provinsi Bengkulu - Deltari Novitasari; Alfian Noor (UNIVED Press, 2022)
The main issue in this research is the low standard of public services at the Bengkulu Provincial Secretariat. This is because the service standards for delivering data in the preparation of performance reports to the Provincial Government are currently not technically structured and do not have special regulations, resulting in the non-optimal preparation of performance reports that can describe real conditions that occur at the time such as the absence of service standards in standard form (information/administrative requirements) in the submission of performance report data. The research method uses descriptive qualitative analysis with SWOT through observation and interviews. The results of the study prove that the most appropriate optimization of public services to improve performance reporting is to carry out a communication strategy, and the achievement of success has been seen from the existence of standard service standards. It is hoped that with this research, the government can improve the development of human resources through a high attitude and work spirit that is oriented to the interests of the community, nation and state and has responsibility with the work environment and organization.